Prevalence of latent tuberculosis and associated factors in patients with chronic kidney disease on hemodialysis - Viviane Ferreira; Cassiane Dezoti da Fonseca; Valdes Roberto Bollela; Elen Almeida Romão; Jose Abrão Cardeal da Costa; Alvaro Francisco Lopes de Sousa; Dulce Aparecida Barbosa (Universidade de São Paulo, 2021)
Objective: to identify the prevalence of latent tuberculosis in patients with chronic kidney disease on hemodialysis and associated factors. Method: a cross-sectional study conducted with 176 patients with chronic kidney disease on hemodialysis. The tuberculin test was performed with the standardized antigen, distributed by the Brazilian Ministry of Health, and the reading occurred after 72 to 96 hours of the application. An association test (Chi-square, Fisher's exact), prevalence ratio, and multivariate regression tests were performed. Results: the prevalence of latent tuberculosis diagnosed through Tuberculosis Skin Test was 8.5% (15/176). The "has/has had diabetes" (aOR: 0.117; 95%CI: 0.015-0.92) and "having regular garbage collection (aOR: 0.076; 95%CI: 0.008-0.702) factors were associated with a lower probability of having a Positive skin test. Conclusion: the low prevalence of latent tuberculosis identified and the factors associated with it reinforce the need for screening for latent tuberculosis infection for diabetics combined with an analysis of previous risk factors and comorbidities.